The Home Learning Environment in the Digital Age—Associations Between Self-Reported “Analog” and “Digital” Home Learning Environment and Children’s Socio-Emotional and Academic Outcomes - Lehrl, Simone; Linberg, Anja; Niklas, Frank; Kuger, Susanne (Frontiers in Psychology, 2021)
We analyzed the association between the analogue and the digital home learning environment (HLE) in toddlers’ and preschoolers’ homes, and whether both aspects are associated with children’s social and academic competencies. Here, we used data of the national representative sample of Growing up in Germany II, which includes 4914 children aged 0-5 years. The HLE was assessed via parental survey that included items on the analogue HLE (e.g. playing word games, reading, and counting) and items on the digital HLE (e.g. using apps or playing with apps). Children’s socio-emotional, practical life skills and academic competencies were assessed via standardized parental ratings. Our results indicate that there are two dimensions of the HLE, an analogue and a digital, that are slightly positively associated, especially in the age group of the under three-year old’s. For toddlers, only analogue HLE activities were associated with better socio-emotional and practical life skills outcomes. However, toddlers with less frequent analogue HLE activities showed greater socio-emotional competencies in households with more frequent digital activities. For preschoolers, digital HLE activities were associated with weaker socio-emotional skills but higher academic skills, although the analogue HLE shows higher effect sizes for the academic outcomes. Our study points out that analogue and digital HLE activities seem to be partly associated, but not interchangeable. Further, they seem to be important variables that can explain individual differences in young children’s socio-emotional, practical life and academic competencies. However, digital media usage at home may also have negative effects on children’s social-emotional competencies. This association needs to be investigated further.